Cross-Border Integration of Chinese Traditional Opera and Animation under Digital Technology - Dai, Jinling; Yaacob, Husaini (European Journal of AI, Computing & Informatics, 2025)
The advancement of digital technology has provided unprecedented opportunities for the cross-border integration of traditional Chinese opera and animation, promoting the innovative development and inheritance of traditional culture. However, there is still a lack of systematic research on the specific paths and impacts of this integration. This article aims to explore how digital technology can promote the combination of traditional Chinese opera and animation, in order to enhance the artistic expressiveness and the effectiveness of its dissemination. In this research, the article adopts qualitative research methods, including text analysis and case studies, to deeply analyze successful works that have integrated opera and animation in recent years, aiming to summarize their artistic characteristics and innovative models. The research finds that the flexibility and creativity of animation can enhance the expressiveness of opera, making stylized movements, character images and storylines more dynamic and visually impactful, thereby attracting a wider audience. In addition, digital technology gives traditional opera elements a new visual context, enabling them to regain new vitality. However, the research also shows that in the process of animating traditional opera, how to find a balance among audience perception, artistic expression and business models remains a challenge that needs to be addressed urgently. Through case analysis and integration with traditional cultural elements, the rational application of digital technology and animation techniques can not only promote the innovative expression of traditional Chinese opera, but also broaden its dissemination channels and enhance its appeal among younger audiences. In the future, the practice of opera animationization needs to explore more diversified forms of expression while maintaining the core value of opera culture, in order to achieve the modernized inheritance of traditional culture.